Peran persepsi harga, kualitas produk, promosi dan lokasi terhadap kepuasan konsumen pada swalayan di Kota Depok - Nurfitri, Ade Rachmawati; Winarsih, Winarsih; Setyaningsih, Endang (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
The availability of products with the category of daily necessities at supermarkets can help the community and loyal customers to fulfill their needs. What's more, supermarkets provide a comfortable, clean shopping place accompanied by air conditioning. Supermarket is a retail business that sells a variety of daily necessities. Therefore, retail business actors need to understand who the consumers are, so that the various products sold in the supermarket are right on target. This research was conducted to find out how the influence of price perception, product quality, promotion and location on consumer satisfaction. The questionnaire instrument was used to collect data with Likert scale measurements, with 120 respondents, namely respondents who had shopped at supermarkets in Depok city with a minimum age limit of 18 years. The method of analysis used is multiple linear regression. The results obtained from this study are that the variables of price perception, product quality, promotion and location partially and simultaneously affect customer satisfaction, and the variable that has the most influence on customer satisfaction is the location variable.